PENINGKATAN KUALITAS HIDUP PENDERITA GAGAL GINJAL KRONIK YANG MENJALANI TERAPI HEMODIALISA MELALUI MIND BODY INTERVENTION DI UNIT HEMODIALISA RSU ROYAL PRIMA MEDAN TAHUN 2019 - Sitorus, Frisnayanti; Sunarti, Sunarti; Buulolo, Fanolonama; Manao, Lukmadil Dakhi Rafael Rianto; Harita, Sanohu Saro (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2019)
Chronic kidney failure is a terminal disease, it can be characterized by a decrease in glomerular filtrationrate and accompanied by urine sediment abnormalities, so patients must undergo renal replacementtherapy such as dialysis (hemodialysis. People with chronic renal failure should undergo lifelonghemodialysis therapy resulting in decreased CRF quality of life, then a complementary treatment was used,namely mind body intervention through prayer spiritual healing therapy to improve health status.The aimof this study was to analyze the improvement in quality of life of patients with chronic renal failureundergoing hemodialysis therapy through mind body intervention. one-group pre post test design, thenumber of samples was 20 respondents using purposive sampling technique.The results showed that therewas an increase in the quality of life of GGK patients through mind body intervention with value of p value=0,000 through the Wilcoxon rank test. Based on the results of the research obtained, it is expected thatpatients with CRF can make mind body intervention as non-pharmacological management to improvequality of life.